2022
DOI: 10.1371/journal.pone.0276681
|View full text |Cite
|
Sign up to set email alerts
|

Associations of maximum and reactive strength indicators with force–velocity profiles obtained from squat jump and countermovement jump

Abstract: Understanding the properties associated with the vertical force–velocity (F–v) profiles is important for maximizing jump performance. The purpose of this study was to evaluate the associations of maximum and reactive strength indicators with the F–v profiles obtained from squat jump (SJ) and countermovement jump (CMJ). On the first day, 20 resistance-trained men underwent measurements for half squat (HSQ) one-repetition maximum (1RM). On the second day, jump performances were measured to calculate the drop jum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…Notably, the calculated FVP may differ if different motor tasks are performed. Nishioka and Okada showed that the FVP variables in SJ and CMJ may be incompatible (14). Moreover, Samozino et al's equation was not formulated using a movement task such as a vertical jump, which considered redundancy and coordination (17,18).…”
Section: Discussionmentioning
confidence: 99%
“…Notably, the calculated FVP may differ if different motor tasks are performed. Nishioka and Okada showed that the FVP variables in SJ and CMJ may be incompatible (14). Moreover, Samozino et al's equation was not formulated using a movement task such as a vertical jump, which considered redundancy and coordination (17,18).…”
Section: Discussionmentioning
confidence: 99%
“…All three variables were moderately correlated to F 0 , but not to the other F-v-P profile parameters. F 0 reflects the maximum concentric force output that the athlete's lower limbs can theoretically produce during ballistic push-off at null velocity (Morin & Samozino, 2016;Nishioka & Okada, 2022;Samozino, et al, 2012). Therefore, the association between CMJ height, UCMJ height and the RSImod BCMJ and F 0 could mean that these variables are indices that evaluate the ability to produce force at lower velocities.…”
Section: Discussionmentioning
confidence: 99%
“…Through the literature, several studies assessed the association between performance variables and the F-v-P profile. A study done by Nishioka and Okada (2022) evaluated the association between drop jump reactive strength index (DJ RSI) and the parameters of F-v-P profiles obtained from Note. CI -confidence interval; SD -standard deviation; BCMJ -bilateral countermovement jump; UCMJ -unilateral countermovement jump; RSImod -reactive strength index modified; BLD -bilateral deficit; F 0 -maximal theoretical force, v 0 -maximal theoretical velocity; P max -maximal theoretical power; Slope -inclination of the force-velocity regression line; Slope opt -magnitude of the difference between actual and optimal inclinations of force-velocity regression lines.…”
Section: Discussionmentioning
confidence: 99%
“…For DJ, the contact and take-off were defined as the time points at which the vertical GRF exceeded or decreased below the threshold (i.e., 20 N), respectively. The DJ height was determined using the flight time method ( 26 , 42 ).…”
Section: Methodsmentioning
confidence: 99%